TEACHER’S STRATEGIES IN THE IMPLEMENTATION OF GLOBAL ENGLISHES IN EXTENSIVE LISTENING: LESSONS LEARNED FROM INDONESIA - Muhammad Handi Gunawan; Jihad Fadillah (Indonesian EFL Journal, 2026)
English role as a global lingua franca necessitates a shift in teaching practices away from traditional native-speaker norms toward an appreciation of diverse English varieties. In the Expanding Circle, conventional instruction often fails to equip learners for real-world communication with varied accents. This study examined the effective strategies EFL teachers use in extensive listening classrooms to integrate Global Englishes (GE) and to assess students’ responses to these diverse materials. This study employed a qualitative case study design, utilizing classroom observations, lecturer questionnaires, and student reflections from one experienced EFL lecturer and approximately 30 undergraduate students at an Indonesian public university. Data were analyzed using thematic analysis. The findings reveal three key strategies: the consistent use of authentic and diverse materials from various global regions, a pedagogical focus on comprehension over accent perfection, and the implementation of structured activities like journals, presentations, and group discussions. Students’ responses were highly positive, showing active participation, enhanced confidence in their own accents, and improved peer interaction. However, students also reported challenges in finding varied resources and understanding certain “strong accents”. In conclusion, the study affirms that moving beyond a native-centric model to integrate GE is a practical necessity for boosting communicative competence. The documented strategies offer an effective pedagogical model for preparing learners for the linguistic realities of a globalized world. These findings contribute an empirically grounded, context-specific pedagogical framework for GE integration in EFL extensive listening instruction in the Indonesian higher education context.